New directions in African military history - Stapleton, Timothy J. (Timothy Joseph), 1967- author. Link
1 online resource.
Keywords: "New Directions in African Military History takes a thematic approach to the history of war and military structures in Africa and highlights the under-researched areas. African Military History represents a relatively new and fast-growing sub-field bridging the previously wide gap between the well-established genres of African History and Military History. Based on a synthesis of existing literature and aimed at a wide readership, this book adopts a broad temporal range and uses select examples to highlight a series of points to cover the pre-colonial to post-colonial eras and offering examples from various parts of the continent. This volume evaluates controversial academic debates examining evidence, research methods, approaches and changing historiographical contexts as well as pointing to potential new areas of research. It comprises seven thematic chapters on ways of war, weapons technology, navies, air power, battles, women combatants and genocide in African history. This volume will be of value to students and scholars alike interested in Modern History, Military History and African History"--